Certainty-uncertainty : And the attitudinal space in between - Cantarini, Sibilla; Abraham, Werner; Leiss, Elisabeth (Studies in language companion series, 2014)
Religious belief is an emotional attitude that is not based on a "certain" experience. Adolescence is a very uncertain stage of life and an unstable faith can mirror this turbulence. The aim of this work is to investigate the discursive construction of religious experience in late adolescence. We asked 230 university students to write about their religious views. Their texts were analyzed using content analysis and critical discourse analysis. We divided the responses into four groups: believers, atheists, doubters and agnostics. The different rhetorical strategies arising from the contrast be.